Eye movements reveal mechanisms underlying attentional biases towards threat. Issue 7 (2nd October 2016) - Sagliano, Laura; D'Olimpio, Francesca; Taglialatela Scafati, Ilaria; Trojano, Luigi
ABSTRACT: Mechanisms underlying attentional biases towards threat (ABTs), such as attentional avoidance and difficulty of disengagement, are still unclear. To address this issue, we recorded participants' eye movements during a dot detection task in which threatening or neutral stimuli served as peripheral cues. We evaluated response times (RTs) in trials where participants looked at the central fixation cross (not at the cues), as they were required, and number and duration of (unwanted) fixations towards threatening or neutral cues; in all analyses trait anxiety was treated as a covariate. Difficulty in attentional disengagement (longer RTs) was found when peripheral threatening stimuli were presented for 100 ms. Moreover, we observed significantly shorter (unwanted) fixations on threatening than on neutral peripheral stimuli, compatible with an avoidance bias, for longer presentation times. These findings demonstrate that, independent of trait anxiety levels, disengagement bias occurs without eye movements, whereas eye movements are implied in threat avoidance.